A Phenomenology of Marijuana Use Among Graduate Students. Issue 1 (2nd January 2016) - Garner, Emily
Abstract: Guided by a hermeneutic-phenomenological methodology, this study focused on gaining an in- depth understanding of the use of marijuana by graduate students, a population which does not fit the usual profile of marijuana users addressed in the field literature, by exploring the experience of being a graduate student who uses marijuana. Semi-structured individual interviews were conducted with seven marijuana users attending a graduate programme of study, with elaboration and clarification of their initial description of their respective experiences dialogically prompted by means of open-ended questions. Five interrelated themes emerged from the analysis of the transcribed interviews, with the central finding indicating that the experience of being a graduate student who uses marijuana involves a process of ongoing negotiation between, on the one hand, messages from society and academia, and, on the other, an inner sense of self and well-being.